Do All Roads Lead to Rome? Genes Causing Dravet Syndrome and Dravet Syndrome-Like Phenotypes - Ding, Jiangwei; Wang, Lei; Jin, Zhe; Qiang, Yuanyuan; Li, Wenchao; Wang, Yangyang; Zhu, Changliang; Jiang, Shucai; Xiao, Lifei; Hao, Xiaoyan; Hu, Xulei; Li, Xinxiao; et al. (Frontiers in Neurology, 2022)
Background Dravet syndrome (DS) is a severe epileptic encephalopathy mainly caused by haploinsufficiency of the gene SCN1A, which encodes the voltage-gated sodium channel NaV1. 1 in the brain. While SCN1A mutations are known to be the primary cause of DS, other genes that may cause DS are poorly understood. Several genes with pathogenic mutations result in DS or DS-like phenotypes, which may require different drug treatment approaches. Therefore, it is urgent for clinicians, especially epilepsy specialists to fully understand these genes involved in DS in addition to SCN1A. Particularly for healthcare providers, a deep understanding of these pathogenic genes is useful in properly selecting and adjusting drugs in a more effective and timely manner. Objective The purpose of this study was to identify genes other than SCN1A that may also cause DS or DS-like phenotypes. Methods A comprehensive search of relevant Dravet syndrome and severe myoclonic epilepsy in infancy was performed in PubMed, until December 1, 2021. Two independent authors performed the screening for potentially eligible studies. Disagreements were decided by a third, more professional researcher or by all three. The results reported by each study were narratively summarized. Results A PubMed search yielded 5,064 items, and other sources search 12 records. A total of 29 studies published between 2009 and 2021 met the inclusion criteria. Regarding the included articles, seven studies on PCDH19, three on SCN2A, two on SCN8A, five on SCN1B, two on GABRA1, three on GABRB3, three on GABRG2, and three on STXBP1 were included. Only one study was recorded for CHD2, CPLX1, HCN1 and KCNA2, respectively. It is worth noting that a few articles reported on more than one epilepsy gene. Conclusion DS is not only identified in variants of SCN1A, but other genes such as PCDH19, SCN2A, SCN8A, SCN1B, GABRA1, GABRB3, GABRG2, KCNA2, CHD2, CPLX1, HCN1A, STXBP1 can also be involved in DS or DS-like phenotypes. As genetic testing becomes more widely available, more genes associated with DS and DS-like phenotypes may be identified and gene-based diagnosis of subtypes of phenotypes in this spectrum may improve the management of these diseases in the future.